Kiai's Leadership in Developing Islamic Boarding School Education Culture - Muhammad, Muhammad; Syukri, Ahmad; Hakim, Lukman (Journal of Educational Research, 2024)
This article analyzes the leadership of Kiai of Islamic Boarding Schools in the development of Islamic boarding school culture in Jambi Province. This article comes from a qualitative descriptive study with data collection through observation, interviews, and documentation. While the stages of data analysis are carried out with the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that Kiai leadership is very much needed in the current era related to the competition between Islamic Boarding Schools in terms of recruiting new genius students. In addition, the Kiai of Islamic Boarding Schools in Jambi Province are able to achieve local, national, and international achievements in the fields of religion, academics and sports from both teachers and students. All of this happened because the Kiai of Islamic Boarding Schools had a spirit of trust and determination in managing the potential of Islamic Boarding Schools to become Islamic Boarding Schools. The development of Islamic Boarding School culture in the form of physical can be seen from the complete facilities and infrastructure by the Kiai of Islamic Boarding Schools. Artikel ini menganalisis kepemimpinan Kiai Pondok Pesantren dalam pengembangan budaya pesantren di Provinsi Jambi. artikel ini berasal dari penelitian deskriptif kualitatif dengan pengumpulan data secara observasi, wawancara, dan dokumentasi. Sedangkan tahapan analisis data dilakukan dengan tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa kepemimpinan Kiai sangat diperlukan pada era sekarang berkaitan dengan adanya persaingan antar Pondok Pesantren dalam hal perekrutan calon santri baru yang jenius. Di samping itu, para Kiai Pondok Pesantren yang berada di Provinsi Jambi mampu meraih prestasi lokal, nasional, serta internasional dibidang agama, akademik serta olahraga baik dari guru maupun dari santrinya. Semua itu terjadi karena Kiai Pondok Pesantren telah memiliki jiwa amanah dan keteguhan dalam mengelola potensi Pondok Pesantren menjadi Pondok. Adapun pembinaan budaya Pondok Pesantren berupa fisik dapat dilihat dari perlengkapan sarana dan prasarana yang lengkap oleh Kiai Pondok Pesantren.